Internalized Shame as a Mediator Between Emotional Neglect and Self-Harming Behavior - Gottschlich, Daniela; Turner, Sarah; Anderson, Michael (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the mediating role of internalized shame in the relationship between emotional neglect and self-harming behavior among adolescents and young adults.Methods and Materials: The research employed a descriptive correlational design and was conducted on a sample of 511 participants aged 16 to 25 from Canada, selected based on the Morgan and Krejcie sample size table. Data were collected using the Self-Harm Inventory (SHI), the Emotional Neglect subscale of the Childhood Trauma Questionnaire–Short Form (CTQ-SF), and the Internalized Shame Scale (ISS). Descriptive statistics and Pearson correlation analyses were conducted using SPSS version 27 to examine relationships between variables. Structural equation modeling (SEM) was performed in AMOS version 21 to test the mediating effect of internalized shame, and model fit indices were evaluated to assess the adequacy of the hypothesized model.Findings: Descriptive statistics showed moderate to high levels of emotional neglect (M = 15.87, SD = 4.21), internalized shame (M = 62.34, SD = 13.76), and self-harming behavior (M = 7.41, SD = 3.19). Pearson correlation analysis revealed significant positive associations between emotional neglect and internalized shame (r = .49, p < .001), emotional neglect and self-harming behavior (r = .41, p < .001), and internalized shame and self-harming behavior (r = .53, p < .001). The SEM results confirmed that internalized shame significantly mediated the relationship between emotional neglect and self-harming behavior (indirect effect: β = .23, p < .001), with the model showing good fit indices (χ²/df = 2.29, CFI = .97, RMSEA = .051).Conclusion: The findings suggest that internalized shame plays a significant mediating role in the pathway from emotional neglect to self-harming behavior, highlighting the importance of addressing shame-related cognitions in preventive and therapeutic interventions for adolescents at risk of self-harm.